How are India’s districts doing on nutrition-related non-communicable diseases? Insights from the National Family Health Survey-4 - Menon, Purnima; Mani, Sneha; Nguyen, Phuong Hong (International Food Policy Research Institute, 2017)
A set of diet-related global non-communicable diseases (NCD) targets, to be achieved by 2025, was endorsed by the World Health Assembly (WHA) in 2013. A sub-set of those targets are directly nutritionrelated. This Data Note describes the current levels of a set of key NCD-related outcomes at the districtlevel in India, summarizing data from the recently released district fact sheets of the National Family Health Survey.